Analogical Dialectics in Religious Language: Beyond Literal/Metaphorical Reductionism - Taheri, Javad (Religions, 2024)
This paper investigates the developmental trajectory of the debate concerning the nature of religious language, particularly the contrast between its literal and metaphorical dimensions, situating it within the broader context of linguistic, philosophical, and theological scholarship. Drawing on contemporary research, it offers a critical evaluation of three major approaches, with a detailed analysis of one in particular. The first two approaches, literalism and metaphoricism, are critiqued for their reductionist frameworks, which fundamentally erode the multifaceted nature of this discourse. The third approach, while avoiding these reductionist pitfalls, still calls for further clarification of the mechanisms underlying the interplay between these elements. Through conceptual analysis and grammatical examination, it demonstrates that this proposal, which posits a dynamic interaction—where neither dimension is subordinate to the other, but rather, they paradoxically coexist—yields a more accurate account. The findings suggest that this dialectical approach surpasses the conventional treatment of the literal–metaphorical nexus, proposing that religious language is not only communicative and comprehensible but also an evolving process in which grammatical perplexity fosters semantic depth and intellectual insight.